Mild Radical Oxidative sp3-Carbon–Hydrogen Functionalization: Innovative Construction of Isoxazoline and Dibenz[b,f]oxepine/azepine Derivatives - Gini, Andrea; Mancheño, Olga García (Synlett, 2016)
Direct carbon–hydrogen bond functionalization has emerged as a powerful synthetic method for the straightforward and modular functionalization of organic molecules. In this account, we described our latest contributions in the area of oxidative sp3-carbon–hydrogen bond functionalization using mild radical oxidants for the construction of structurally important heterocycles. We have developed two new methodologies in which a new class of substrate and an uncommon nucleophilic reagent have been introduced to the existing palette of reaction partners for oxidative carbon–hydrogen functionalization. To achieve these results, the 2,2,6,6-tetramethylpiperidinyloxyl (TEMPO) radical and a benzoyl peroxide/copper(I) system have been employed as oxidants for the dehydrogenative one-pot synthesis of N-alkoxycarbonyl-protected isoxazolines from hydroxylamines and for the synthesis of dibenz[b,f]oxepines, dibenzo[b,f]thiepines, and dibenz[b,f]azepines from simple xanthenes, thioxanthenes, and acridanes, respectively.1 Introduction2 2,2,6,6-Tetramethylpiperidinyloxyl-Mediated Dehydrogenative Formation and Trapping of Unstable Nitrones: Synthesis of N-Alkoxycarbonyl-Protected Isoxazoline Derivatives3 Oxidative sp3-Carbon–Hydrogen Bond Functionalization and Ring Expansion with Trimethylsilyldiazomethane: Synthesis of Dibenzoxepines, Dibenzothiepines, and Dibenzazepines4 Conclusions and Outlook
Keywords: carbon–hydrogen functionalization; oxidations; radicals; peroxides; heterocycles